Kress smoothing transformation for weakly singular Fredholm integral equation of second kind - Mohamed Saeed Bawazir, Hassan (2006)
This work investigates a numerical method for the second kind Fredholm integral equation with weakly singular kernel k(x, y), in particular, when k(x, y) = ln |x-y|, and k(x, y) = |x-y|-a, -1 = x, y = 1, 0 < a < 1. The solutions of such equations may exhibit a singular behaviour in the neighbourhood of the endpoints x = Â±1. We introduce a new smoothing transformation based on the Kress transformation for solving weakly singular Fredholm integral equations of the second kind, and then using the Hermite smoothing transformation as a standard. With the transformation an equation which is still weakly singular is obtained, but whose solution is smoother. The transformed equation is then solved numerically by product integration methods with interpolating polynomials. Two types of interpolating polynomials, namely the Gauss-Legendre and Chebyshev polynomials, have been used. Numerical examples are presented to investigate the performance of the former.